A Case Study on the Implementation of Inclusive Education for Hearing-Impaired Students in Primary Schools (Jurnal Ilmiah Sekolah Dasar, 2024)
Inadequate educational services for students with hearing impairments affect not only their academic achievement but also their long-term social, economic, and psychological well-being. This study aims to explore the quality of inclusive education services for students with hearing impairments by analyzing the components of input, process, and output as indicators of implementation effectiveness. Employing a qualitative approach with a multi-site case study design, data were collected through in-depth interviews, observations, and document analysis involving 26 informants, including educators, school staff, parents, and representatives from related institutions. Thematic analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that limitations in facilities, adaptive learning media, and teacher competence are major challenges within the input component. In the process component, curriculum adaptation, instructional modifications, and cross-sector collaboration contribute positively to student engagement and interaction. Regarding output, the study found significant progress in students’ academic and social abilities, although further development in independence and communication skills remains necessary. These findings highlight the importance of policy support, professional development for educators, and the provision of inclusive learning resources to enhance the quality of education services for students with hearing impairments.